Examining the Impact of Minimum Handgun Purchase Age and Background Check Legislation on Young Adult Suicide in the United States, 1991–2020 - Fridel, Emma E.; Zimmerman, Gregory M.; Arrigo, Shayna R. (American journal of public health (1971), 2024)
Objectives. To examine the independent and joint effects of state legislation on minimum age for purchasing handguns and background checks on the suicide of young adults aged 18 to 20 years. Methods. We used negative binomial regressions with fixed effects for year and generalized estimating equations for state to estimate the effects of state legislation on annual counts of firearm, nonfirearm, and total young adult suicides in all 50 US states from 1991 to 2020. Results. Minimum age laws decreased the incidence rate of firearm suicide among young adults, an effect that was amplified in states with permit to purchase laws; there was no effect on the nonfirearm or total suicide rate. Permit to purchase laws significantly decreased the young adult firearm suicide incidence rate by 39% (incidence rate ratio [IRR] = 0.61; 95% confidence interval [CI] = 0.51, 0.74) and the overall suicide incidence rate by 14% (IRR = 0.86; 95% CI = 0.75, 0.99), with no effect on the nonfirearm suicide rate. Conclusions. Permit to purchase laws are a more promising avenue for reducing young adult suicides than are age-based restrictions. ( Am J Public Health. 2024;114(8):805–813. https://doi.org/10.2105/AJPH.2024.307689 )